Fibroblast growth factor receptor-1 associated myeloproliferative neoplasm and T-lymphoblastic lymphoma - Gayathri Gopan; T M Anoop; N P Prakash; Rakul Nambiar; R Krishnachandran (Wolters Kluwer Medknow Publications, 2017)
Myeloid and lymphoid hematological malignancies with eosinophilia and abnormalities of fibroblast growth factor receptor-1 (FGFR1) result from the formation of abnormal fusion genes that encode constitutively activated tyrosine kinases. The WHO classification (2008) of hematolymphoid neoplasms recognizes a category of myeloid and lymphoid neoplasms with eosinophilia and abnormalities of FGFR1. Here, we present the case of a 30-year-old-woman who was diagnosed with T-lymphoblastic lymphoma from lymph node biopsy and myeloproliferative neoplasm with eosinophilia from bone marrow studies. She was treated with combination chemotherapy with cyclophosphamide, vincristine, doxorubicin, and dexamethasone (Hyper-CVAD regimen) and is on maintenance chemotherapy for the past 2 months. We present this case to create awareness among physicians about this rare condition associated with dual malignancies.